Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1097/00000658-199907000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Impact of Documented Eradication of Breast Cancer Axillary Lymph Node Metastases Before Surgery in Patients Treated With Neoadjuvant Chemotherapy

Abstract: ObjectiveTo determine the incidence and prognostic significance of documented eradication of breast cancer axillary lymph node (ALN) metastases after neoadjuvant chemotherapy. Summary Background DataNeoadjuvant chemotherapy is the standard of care for patients with locally advanced breast cancer and is being evaluated in patients with earlier-stage operable disease. MethodsOne hundred ninety-one patients with locally advanced breast cancer and cytologically documented ALN metastases were treated in two prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
206
1
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(225 citation statements)
references
References 26 publications
12
206
1
5
Order By: Relevance
“…There is clear evidence that NAC downstages posi tive axillary nodes in a proportion of patients. Early studies have shown that NAC can completely clear axillary metastases in approximately 23% of patients with locally advanced breast cancer [6] , rates that have increased to 40%60% with the use of targeted therapies [7] . Axillary complete downstaging after NAC has been correlated with better prognosis and assessment of residual disease after NAC is important not only in determining the prognostic information but also in selecting candidates for further systemic and radiation therapy treatment [7,8] .…”
Section: Rationale For Neoadjuvant Treatment In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…There is clear evidence that NAC downstages posi tive axillary nodes in a proportion of patients. Early studies have shown that NAC can completely clear axillary metastases in approximately 23% of patients with locally advanced breast cancer [6] , rates that have increased to 40%60% with the use of targeted therapies [7] . Axillary complete downstaging after NAC has been correlated with better prognosis and assessment of residual disease after NAC is important not only in determining the prognostic information but also in selecting candidates for further systemic and radiation therapy treatment [7,8] .…”
Section: Rationale For Neoadjuvant Treatment In Breast Cancermentioning
confidence: 99%
“…The number of residual metastastic axillary nodes after NAC has been established as an important prog nostic factor for disease free survival [6] . Axillary response after NAC is a better prognostic factor than response of the primary tumor [6,8,27] .…”
Section: Minimal Sln Involvement In the Sln (Isolated Tumor Cells)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is enough evidence to show the benefit from Anthracycline combination chemotherapy. [8][9][10][11][12] Data from RCTs show that the rate of breast conserving surgery and pathologic complete response was significantly higher for patients receiving taxanes (Docetaxel). [13][14][15][16][17][18][19] No consensus exists whether anthracycline and taxanes can be used in combination or in sequence.…”
Section: Introductionmentioning
confidence: 99%
“…In that respect, pre-chemotherapy sentinel node biopsy is revealed as advantageous. We know that chemotherapy will result in the complete remission of axillary lymph node metastases in 20-40% of patients diagnosed with lymph node involvement prior to treatment [3]. Radiotherapy should later be offered to those patients, even if there has been complete remission of the axillary lymph node lesions.…”
mentioning
confidence: 99%